Notch Intracellular Domain Plasmid Delivery via Poly(Lactic-Co-Glycolic Acid) Nanoparticles to Upregulate Notch Pathway Molecules - Messerschmidt, Victoria L.; Chintapula, Uday; Kuriakose, Aneetta E.; Laboy, Samantha; Truong, Thuy Thi Dang; Kydd, LeNaiya A.; Jaworski, Justyn; Pan, Zui; Sadek, Hesham; Nguyen, Kytai T.; Lee, Juhyun (Frontiers in Cardiovascular Medicine, 2021)
Notch signaling is a highly conserved signaling system that is required for embryonic development and regeneration of organs. When the signal is lost, maldevelopment occurs and leads to a lethal state. Delivering exogenous genetic materials encoding Notch into cells can reestablish downstream signaling and rescue cellular functions. In this study, we utilized the negatively charged and FDA approved polymer poly(lactic-co-glycolic acid) to encapsulate Notch Intracellular Domain-containing plasmid in nanoparticles. We show that primary human umbilical vein endothelial cells (HUVECs) readily uptake the nanoparticles with and without specific antibody targets. We demonstrated that our nanoparticles are nontoxic, stable over time, and compatible with blood. We further demonstrated that HUVECs could be successfully transfected with these nanoparticles in static and dynamic environments. Lastly, we elucidated that these nanoparticles could upregulate the downstream genes of Notch signaling, indicating that the payload was viable and successfully altered the genetic downstream effects.